Upaya Peningkatan Hasil Belajar Siswa Pada Pembelajaran Alquran-Hadits Melalui Penerapan Model M2E (Mapping, Matrix And Elaboration) - Ading Ading (Fakultas Tarbiyah, Universitas Ibrahimy, 2022)
This research aims to know the competence of teacher in designing the implementation of M2E learning model on the Alquran-Hadits subject matter with theme “definition of hadits, sunah, khobar and atsar,” the implementation process of M2E learning model on the Alquran-Hadits subject matter with theme “definition of hadits, sunah, khobar and atsar,” and the effectiveness of M2E learning model implementation on the Alquran-Hadits subject matter with theme “definition of hadits, sunah, khobar and atsar,” in the grade 10th IPA of Madrasah Aliyah. Research method used in this article is classroom action research. The result research is 1) the competence of teacher in planning the learning of Alquran-Hadits with theme “definition of hadits, sunah, khobar and atsar” by M2E learning model, from cycle to cycle showed a good increase with the results of 62,14% for the first cycle and 80% for the second cycle, 2) the competence of teacher in implementing the learning of Alquran-Hadits with theme “definition of hadits, sunah, khobar and atsar” by M2E learning model, from cycle to cycle showed a good increase with the results of 61,5% for the first cycle and 78% for the second cycle, 3) Student learning outcomes in the first cycle 71,05; and second cycle 80,53.